Pengaruh Corporate Governance, Rasio Pajak, Profitabilitas dan Ukuran Perusahaan Terhadap Struktur Modal - Santhi, I Gusti Ayu Padma; Sudjarni, Luh Komang (E-Jurnal Manajemen, 2015)
The funding decision is important for the company. This is because the level of use regarding the proportion of debt to equity in the level of investment financing. The company must decide whether to use internal funds first or external funds to finance investment. Financial managers must consder the fctors that afect the structure. This stdy examned the corporate governance, tax ratio, profitability, and size of the company on the capital structure.Indonesia Stock incoming ratings (CGPI) 2010-2012 will be the study population. Determination of the sample using purposive sampling method and determination through certain criteria then obtained a sample of 55 companies.Multiple regression analysis was used to test and obtain results that corporate governance, tax ratio, profitabilits, and the size of the reactor Integration simultaneouslycapital structure. Partial test results to obtain the result that significant ngative efect on the profitbility of cpital strcture and frm sze significant postive efect on the cpital strcture. Meanwhile, corporate governance and the corporate tax rate has no effect on the capital structure.
Keywords: Capital Structure, Corporate Governance, Corporate Tax Ratio, Profitability, Company Size